Investigations on the models of face rockfills for slope stability of coal mine dumps during the restoration - Tosun, Yıldırım İsmail (International Society for Rock Mechanics, 2015)
The bigger mine waste dumps create the greater the issue to encounter in situ ground conditions. Landfill rock waste makes an inadequate strength and economic issue of the reclamation work is more difficult, especially in determination of slope stability. A clear differentiation based on the lump-size rock type and soil distribution and compression in the field of reclamation. GEO5 FEM, Rocklab and Stereonet7 programs performed with four rockfill modeling and stability analysis for A1, A2, A3 and A4 rock fills models where rock fills of the dump slope were limited. Anisotropic rockfill and soil mixture models were made in laboratory scale. Heterogeneous geotechnical parameters were analyzed. Regarding the topographic maps produced in the 1/1000 scale with field work and the structural cross sections of rock fill models conducted on laboratory experiments, the physical and mechanical properties for each A1, A2, A3 and A4 Models. A1, A2 slopes were close to stable state that showed to be slight safety risk. However, GEO5 programs with limestone fill model through FEM program exhibited stability with A3 and A4.